1998
DOI: 10.2307/3284600
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Rhabdochona Railliet, 1916 (Nematoda: Rhabdochonidae) from Endemic Goodeids (Cyprinodontiformes) from Two Mexican Lakes

Abstract: A new species of Rhabdochona from 2 species of freshwater fishes, Alloophorus robustus and Goodea atripinnis, is described from 2 lakes of the Mesa Central of Mexico. Rhabdochona lichtenfelsi n. sp. belongs to a group of species possessing inconspicuous bifurcated deirids and a prostom armed with 10 large teeth. It is distinguished from them because the left spicule is shorter, the tip is bifurcate, and both spicules lack a reflected dorsal barb. The new species most closely resembles Rhabdochona catostomi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the meanwhile, many new species of Rhabdochona have been described mainly from previously little-explored regions of the Americas, Africa and Asia, so that the number of nominal species has approximately been doubled (Moravec 2007a). However, even though some recently described species have also been studied by SEM (Sánchez-Alvarez et al 1998; CaspetaMandujano and Moravec 2000; Caspeta-Mandujano et al , 2005Cremonte et al 2002;Mejía-Madrid and Pérez-Ponce de León 2003;Ramallo 2005;Moravec and Muzzal 2007;Moravec et al 2008Moravec et al , 2009, descriptions of the majority of these nematodes (see e.g., Ghazi et al 2003;Kakar et al 2006Kakar et al , 2008aKakar and Bilqees 2007a, b, c) became again inadequate, not corresponding to the requirements of current nematode taxonomy. Mejía-Madrid et al (2007a) have recently published an interesting paper reporting results of the phylogenetic analysis of 40 Rhabdochona spp., including all 21 at that time considered valid in the Americas, based on the cladistic analysis of 51 morphological characters.…”
Section: Taxonomy and Classificationmentioning
confidence: 99%
“…In the meanwhile, many new species of Rhabdochona have been described mainly from previously little-explored regions of the Americas, Africa and Asia, so that the number of nominal species has approximately been doubled (Moravec 2007a). However, even though some recently described species have also been studied by SEM (Sánchez-Alvarez et al 1998; CaspetaMandujano and Moravec 2000; Caspeta-Mandujano et al , 2005Cremonte et al 2002;Mejía-Madrid and Pérez-Ponce de León 2003;Ramallo 2005;Moravec and Muzzal 2007;Moravec et al 2008Moravec et al , 2009, descriptions of the majority of these nematodes (see e.g., Ghazi et al 2003;Kakar et al 2006Kakar et al , 2008aKakar and Bilqees 2007a, b, c) became again inadequate, not corresponding to the requirements of current nematode taxonomy. Mejía-Madrid et al (2007a) have recently published an interesting paper reporting results of the phylogenetic analysis of 40 Rhabdochona spp., including all 21 at that time considered valid in the Americas, based on the cladistic analysis of 51 morphological characters.…”
Section: Taxonomy and Classificationmentioning
confidence: 99%
“…Xiphophorus hellerii also has been introduced to Hidalgo (Culumber et al, 2013), although its helminthofauna has not been reported. Species of Rhabdochona are well known for host specialization at the family, genus and species level (Sánchez-Álvarez et al, 1998;Mejía-Madrid and Pérez-Ponce de León, 2003). Rhabdochona xiphophori originally was described in Xiphophorus sp.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sánchez-Alvarez et al (1998), 97 nominal species have so far been described. Twenty one species and subspecies have been reported from America: Rhabdochona acuminata (Molin, 1860), R. californiensis Maggenti, Abdel-Rahman et Del Prado, 1992, R. canadensis canadensis Moravec et Arai, 1971, R. canadensis bifilamentosa Moravec et Huffman, 1988, R. cascadilla Wigdor, 1918, R. catostomi Kayton, Kritsky et Tobias, 1979, R. cotti Gustafson, 1949, R. cubensis Moravec et Coy Otero, 1987, R. decaturensis Gustafson, 1949, R. kidderi kidderi Pearse, 1936, R. kidderi texensis Moravec et Huffman, 1988, R. kisutchi Margolis, Moravec et McDonald, 1975, R. lichtenfelsi Sánchez-Alvarez, García-Prieto et Pérez-Ponce de León, 1998, R. longleyi Moravec et Huffman, 1988, R. milleri Choquette, 1951, R. ovifilamenta Weller, 1938, R. paxmani Maggenti, Abdel-Rahman et Del Prado, 1992, R. rotundicaudatum Byrne, 1992, R. salmonis Maggenti, Abdel-Rahman et Del Prado, 1992, R. uruyeni Díaz-Ungría, 1968, and R. zacconis Yamaguti, 1936.…”
Section: Discussionmentioning
confidence: 99%
“…Three species and subspecies of Rhabdochona have so far been reported from fresh waters in Mexico: Rhabdochona kidderi kidderi Pearse, 1936 from Rhamdia guatemalensis (Günther), Ogilbia pearsei (Hubbs), and Gambusia yucatana Regan in cenotes (=sinkholes), cave waters and other water bodies in Yucatán; R. kidderi texensis Moravec et Huffman, 1988 from Cichlasoma fenestratum (Günther) and C. urophthalmus (Günther) from Yucatán and from Catemaco Lake, Veracruz; R. lichtenfelsi Sánchez-Alvarez, García-Prieto et Pérez-Ponce de León, 1998 from Goodea atripinnis Jordan, Alloophorus robustus (Bean) and Neoophorus diazi (Meek) in Pátzcuaro and Cuitzeo Lakes (Moravec 1998).…”
mentioning
confidence: 99%